Erythroxylaceae endémicas del Perú - León, Blanca (2006)
The Erythroxylaceae are represented in Peru by 27 species in the genus Erythroxylum (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all shrubs and trees. Here we recognize four endemic species, which are found in the Tropical Costal Desert and Humid Lowland Amazonian Forests regions, between 150 and 720 m elevation. No endemic Erythroxylaceae have been recorded within Peru’s protected areas system.